Race, Gender, and Work/Family Policy - Nancy E. Dowd (Washington University Journal of Law & Policy, 2004)
In this Article, I argue that our work/family policy must be race and gender conscious in order to affirmatively structure law and policy to achieve egalitarian goals. We have had the contrary experience in other areas of social policy. Housing and tax policies, for example, historically and currently have had a disproportionately negative impact in terms of race and gender. These examples tell us that race and gender consciousness in framing work/family policy is essential. If policy can be framed, consciously or unconsciously, to foster inequality, hierarchy, and segregation, it should also be possible to frame policy to do the opposite: to expressly attack subordination and affirmatively support equality, dignity, and well-being.
Keywords: Parental leave; Race discrimination in employment; Sex discrimination in employment